Manejo Geral de Ovinos em Sistema de Semi Confinamento na Escola de Medicina Veterinária e Zootecnia - EMVZ/UFT. - Sales, Rogel dos Santos (Universidade Federal do Tocantins, 2023)
The objective of this report was to highlight the experiences acquired during the routine of the curricular traineeship, in the sector of ovine breeding of the School of Veterinary Medicine and Animal Science - EMVZ / UFT. Sheep farming is in great expansion in the country, as the demand for animal protein by the market is increasing. Because of this, their products have been gaining more space on the consumer desk. In the state of Tocantins there was a great growth over the years, which promoted the generation of income to small producers and motivating the big producers. During the supervised internship, it was possible to follow the routine and good practices of nutritional management with the preparation of concentrate, silage and hay, besides the management of pasture, with implementation of irrigation and fertilization. In the reproductive management, the directed natural mating technique was done. Sanitary management was done according to need, respecting the maximum period of fifteen days, plus the equipment and utensils were cleaned and disinfected three times a week. The practices developed in the sheep industry allowed greater learning, with knowledge that will serve as the basis for an effective zootechnical work in the labor market.